Penguatan Pemahaman Penilaian Pembelajaran Matematika Mahasiswa Calon Pendidik melalui Kegiatan Bedah Buku - Nur Wiji Sholikin; Pratiwi Dwi Warih Sitaresmi; Ririn Wahyu Ningsih; Ma’rifatul Jannah; Riqqi Quluby (Sejahtera: Pengabdian Kepada Masyarakat, 2026)
Learning assessment is a crucial competency that prospective teacher students must master, particularly in mathematics. However, understanding of learning assessment is often theoretical and not yet integrated with learning practices. This community service activity aims to strengthen students' understanding of mathematics learning assessment through a book review. The activity was conducted at the Ahmad Dahlan Institute in Probolinggo, involving 30 prospective teacher students. The method used was a participatory-educational approach through preparation, implementation, and evaluation. The activity involved group discussions, literature analysis, and presentations of the book reviews, facilitated by the community service team. The results showed that the book reviews improved students' understanding of the concept of mathematics learning assessment, fostered reflective skills, and raised awareness of the importance of alignment between learning objectives, learning strategies, and assessment techniques. This activity made a positive contribution to strengthening assessment literacy in prospective teacher students and can serve as a model for relevant community service activities in higher education. Keywords: mathematics learning assessment; book review; assessment literacy; prospective teacher students; community service